PROPAGASI IN VITRO KALIANDRA MERAH (Calliandra calothyrsus Meisn.) I: PERKECAMBAHAN BIJI DAN INISIASI TUNAS DARI EKSPLAN HIPOKOTIL DAN NODUS - Idris, Muhammad; Asman, Auzia; Sorel, Deni; Joniarti, Edi; Mohtar, Ulfa; Harmailis, Harmailis; Nefri, John; Salivia, Salivia (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
The red calliandra is a fuel wood crops that gave benefit for people. Recently, it is getting wide attention due to its important use as biofuel in industrial scale. The massive propagation is needed to meet industrial needs. Beside the use of conventional seedling production technique, the use of tissue culture for mass propagation is one of the alternatives to address this problem. This research was conducted to develop standard protocol for micropropagation of red calliandra through tissue culture. Here, the first step for that purpose was reported. The MS medium was used for basal media treatment. The seed source was stored for eight months under 5oC. This research was carried out in two stages i.e. 1) seed germination test and 2) shoot initiation and multiplication treatment. Each stage was arranged in experimental method. The result showed that seed were pre-treated with warm water (40oC) gave 62.5% germination under red light when compared to control (37.5%, pre-treated with water at 25oC under white light) three days after planting. Conversely, there is no striking differences of germinated seed percentages between light treatment at 25oC. Furthermore, it was found that addition of 2 mg/L BAP gave better result in shoot initiation and number of shoots formed from nodal explants after four weeks in treatment media. These results indicated that mass propagation of red calliandra can be done through tissue culture where multiplication stage is one of the important steps to produce multiple shoots only from single nodal explant.